ALAT PERAGA EDUKATIF SEBAGAI ALTERNATIF METODE PENGAJARAN PEMAHAMAN PERSAMAAN DASAR AKUNTANSI BAGI SISWA SMA TARSISIUS 1 - Imelda, Elsa; Steven Jong; Parcella Glatia Elfenso (Jurnal Serina Abdimas, 2025)
Many people believe that in the era of increasingly advanced digitalization, automation in the accounting field has taken away the role of accountants. Financial reporting is easily generated by Accounting software. Artificial Intelligence technology even makes it easier for manager level to analyze data. So many people say there is no need to study Accounting. However, this understanding is actually not correct. A basic understanding of accounting is actually important and can help accountants more easily adapt to AI and integrate the information obtained for decision making. Accounting Fundamentals remain an irreplaceable foundation in the accounting profession. High school students need to be taught Accounting but often find it difficult to learn Accounting. In fact, quite a few people avoid accounting because accounting is close to mathematics which requires mastering calculation techniques. The Merdeka Belajar Curriculum which allows students to choose their specialization causes Accounting to become an optional subject, not a mandatory subject. Therefore, the Untar PKM team went directly to Tarsisius 1 High School in developing the Accounting Laboratory there. Students who took the Merdeka Belajar Kampus Merdeka together with Untar lecturers came to Tarsisius 1 High School Jakarta to directly teach Accounting material. The initial material that is fundamental to Accounting lessons is understanding the basic accounting equations. So that students can more quickly understand the teaching material regarding basic accounting equations, the PKM team developed interesting educational teaching aids so that students can understand the material more quickly. ABSTRAK Banyak anggapan mengatakan di era digitalisasi yang semakin maju, otomatisasi di bidang Akuntansi telah merenggut peran akuntan. Pelaporan keuangan dengan mudah dihasilkan oleh software Akuntansi. Teknologi Artificial Intelligence bahkan memudahkan level manager untuk menganalisis data. Sehingga banyak yang mengatakan tidak butuh untuk belajar Akuntansi. Namun sebenarnya pemahaman tersebut tidaklah benar. Pemahaman dasar Akuntansi justru penting dan dapat membantu akuntan lebih mudah beradaptasi dengan AI dan mengintegrasikan informasi yang diperoleh untuk pengambilan keputusan. Fundamental Akuntansi tetap menjadi fondasi yang tidak dapat tergantikan dalam profesi akuntan. Siswa SMA perlu untuk diajarkan Akuntansi tetapi seringkali merasa kesulitan untuk belajar Akuntansi. Bahkan tak sedikit yang menghindari Akuntansi karena Akuntansi dekat dengan ilmu matematika yang perlu menguasai teknik berhitung. Kurikulum Merdeka yang membebaskan siswa memilih peminatan menyebabkan Akuntansi menjadi Pelajaran pilihan, buka pelajaran wajib. Oleh karena itu tim PKM Untar terjun langsung ke SMA Tarsisius 1 dalam pengembangan Laboratorium Akuntansi di sana. Mahasiswa yang mengambil Merdeka Belajar Kampus Merdeka beserta dengan dosen Untar mendatangi SMA Tarsisius 1 Jakarta untuk langsung mengajarkan materi Akuntansi. Materi awal yang menjadi fundamental pelajaran Akuntansi adalah pemahaman persamaan dasar Akuntansi. Agar siswa lebih cepat memahami materi ajar mengenai persamaan dasar Akuntansi, tim PKM mengembangkan Alat Peraga Edukatif yang menarik agar siswa dapat memahami materi dengan lebih cepat.